The possibilities of temporary reintroduction of border control at the internal borders of the Schengen Area in the light of current challenges - Doliwa-Klepacka, Anna (Katolicki Uniwersytet Lubelski Jana Pawła II, 2021)
The creation of the Schengen Area was one of the greatest, most socially appreciated achievements of cooperation between 22 Member States of the European Union and Iceland, Liechtenstein, Norway and Switzerland. The rules on crossing the borders of European Union Member States are common policies subject to specific regimes, but membership of the Schengen Area in particular has numerous consequences in terms of, among other things, border controls, as defined in the Schengen Borders Code. One of the most important of these is the abolition of controls at the internal borders of the countries which make up the Area. The adoption of common rules has not, however, deprived the countries which make up the Schengen Area of certain prerogatives to restore border control at internal borders in exceptional cases. This justification is, in particular, a serious threat to public order or internal security. France made the first use of this possibility on 21.10.2006 by reintroducing control at the land border with Spain for a few hours because of the Youth Days of radical young Basques in Saint-Pée-sur-Nivelle and demonstration organised in Bayonne by the support committee of Philippe Bidart. Since then, the countries have made repeated use of the instrument available and, in particular, the year 2020, which runs in the shadow of COVID-19, brings new challenges in this regard. The submitted article will analyse the possibility of temporary reintroduction of border control at the internal borders of the Schengen Area precisely in the context of the current challenges of the modern world. Utworzenie Strefy Schengen było jednym z największych, najbardziej docenianych społecznie, osiągnięć współpracy 22 państw członkowskich Unii Europejskiej oraz Islandii, Liechtensteinu, Norwegii i Szwajcarii. Zasady przekraczania granic państw członkowskich Unii Europejskiej należą do polityk wspólnych, poddanych szczególnym reżimom, ale szczególnie członkostwo w Strefie Schengen wiąże się z licznymi konsekwencjami w zakresie m.in. kontroli granicznej, określonymi w Kodeksie granicznym Schengen. Jedną z najważniejszych jest zniesienie kontroli na granicach wewnętrznych państw tworzących tę Strefę. Przyjęcie wspólnych reguł nie pozbawiło jednak państw tworzących Strefę Schengen pewnych prerogatyw do przywrócenia kontroli granicznej na granicach wewnętrznych w wyjątkowych przypadkach. Takim uzasadnieniem jest w szczególności poważne zagrożenie dla porządku publicznego lub bezpieczeństwa wewnętrznego. Po raz pierwszy z tej możliwości skorzystała Francja 21 października 2006 r. przywracając na kilka godzin kontrolę na granicy lądowej z Hiszpanią z uwagi na Dni Młodzieży radykalnych młodych Basków w Saint-Pée-sur-Nivelle oraz demonstracje zorganizowane w Bayonne przez komitet wspierający Philippe'a Bidarta. Od tego czasu państwa wielokrotnie korzystały z dostępnego instrumentu. Zwłaszcza rok 2020, który upłynął w cieniu COVID-19 przyniósł nowe wyzwania w tym zakresie. W przedłożonym artykule dokonana zostanie analiza możliwości tymczasowego przywrócenia przez państwa kontroli granicznej na granicach wewnętrznych Strefy Schengen właśnie w kontekście aktualnych wyzwań współczesnego świata.